African American female leadership in major motion pictures : from marginalized to mainstream - Worley, Tracy L. F. (London ; New York : Routledge, 2024)
"This book explores the factors contributing to the under-representation of African American female directors in mainstream cinema leadership. It also unmasks the potential strategies African American female film directors might pursue to reduce this inequity. Author Tracy L. F. Worley draws on research around ethics to conclude that there are specific consequences of the male gaze on women in cinema leadership, especially African American female directors of box office cinema. Combining extensive analysis of ethics and ethical stance relative to the motion picture industry with perspectives from working African American female directors, the text discusses the ethical considerations and historical inequities, including the male gaze, and uses those findings to define how the inequities can be opportunities. The efficacy model for cinematic leadership is presented as a mechanism for viewing obstacles through the lenses of gender, ethnicity, and culture so they become drivers for African American women to achieve success. Ideal for students of directing and filmmaking, as well as aspiring professional filmmakers wishing to gain a better understanding of the industry as it stands today"--
Keywords: African Americans in the motion picture industry; African American women motion picture producers and directors; African American women in motion pictures; Motion picture industry -- United States -- History; Motion pictures -- United States -- History; Motion pictures -- Social aspects -- United States -- History; PERFORMING ARTS / Film & Video / General